Exploring the understanding of how parenting influences the children's nutritional status, physical activity, and BMI - Kocaadam-Bozkurt, Betül; Sözlü, Saniye; Macit-Çelebi, Melahat Sedanur (Frontiers in Nutrition, 2023)
Aim: Parental behaviors and the home environment are two of the most effective ways to adopt healthy eating and active lifestyles. For this reason, it is crucial to understand children's nutritional habits, analyze the dynamics related to parental factors, diagnose and treat childhood obesity in the early period, and prevent adulthood obesity. This study aimed to explore how parenting influences children's nutritional status, physical activity, and BMI. Methods: The study involved 596 children with their parents. The data were collected through face-to-face interviews using the survey method. The survey consists of descriptive information (age, gender, educational status), anthropometric measurements, nutritional habits, Family Nutrition and Physical Activity Scale (FNPA), International Physical Activity Questionnaire, and 24-hour dietary recall. The Mean Adequacy Ratio (MAR) was applied to assess dietary adequacy. Results: Most mothers and fathers were overweight or obese(61.6 % and 68.7%, respectively). 38.6% of boys and 23.1% of girls were overweight or obese. The FNPA score was positively correlated with MAR(p<0.05). Multiple linear regression analysis revealed that children's BMI was negatively correlated with FNPA score, while maternal BMI and father's BMI were positively correlated(p<0.05). Furthermore, dietary energy was not associated with the child's BMI but with dietary adequacy(p<0.05). There was no evidence that family impacted children's physical activity. Conclusion: This study supports the parenting that influences children's dietary intake and BMI. Adequate and balanced nutrition, regardless of dietary energy, may affect children's body weight. Family plays a significant role in influencing and forming children's lifestyle-related behaviors. Children's healthy eating and physical exercise habits can be encouraged through school-based programs involving families.